THE EFFECT OF FAMILY COUNSELING ON ANXIETY DURING PRE-ERUPTION AMONG MERAPI MOUNT RESIDENTS - Ilma Widiya Sari; Ahmad Syamsul Bahri; Vina Asna Afifah (LPPM Universitas Duta Bangsa Surakarta, 2022)
Pre-eruption is one of the factors that trigger anxiety because residents cannot predict when a disaster will occur. Providing counseling with a family approach is a process of support in dealing with problems so that it can reduce anxiety. This study to examine the effect of family counseling on reducing anxiety during pre-eruption. It was quasi-experimental one-group design with a pre-test and post-test. There were 49 residents with moderate to severe anxiety using purposive sampling. The measurement of anxiety score using Zung Self-Rating Anxiety Scale. The bivariate analysis was carried out by parametric test using paired t-test. The result showed that p-value 0,00 (p < 0,05), indicated a significant difference anxiety score in pre-test and post-test. There was an effect of family counseling on anxiety during pre-eruption among residents. Counseling can be used as an intervention in the family to reduce anxiety.